Urinary aflatoxin M1 in Port-au-Prince and a rural community in north-east Haiti. Issue 6 (2nd June 2016) - Schwartzbord, Jeremy R.; Leroy, Jef L.; Severe, Linda; Brown, Dan L.
ABSTRACT: Aflatoxins (AFs) are hepatocarcinogenic mycotoxins that can contaminate grains and oil seeds in tropical and sub-tropical areas and have been detected in maize and peanut products of Haiti. The first objective was to assess human exposure to AFs among Haitians at an urban hospital (GHESKIO) and a rural health centre (HCBH). The second objective was to test the association between AF exposure and reported dietary intake of potentially contaminated foods, such as maize, peanut products and milk. Measurement of urinary AFM1 by HPLC revealed that among 367 participants 14% and 22% at GHESKIO and HCBH, respectively, had detectable AFM1. The maximum and median AFM1 concentrations for all detected samples were 700 pg AFM1 ml –1 and 11.7 pg ml –1, respectively. Detection of AFM1 was significantly associated with peanut consumption ( p  < 0.05). Controlling for diet and age group in a logit model, patients who reported peanut consumption the day of the survey and patients from HCBH had greater log odds of excreting detectable AFM1 ( p  < 0.001 and 0.002, respectively); females had lower log odds ( p  = 0.020). Recalled frequency of consuming non-dairy animal-sourced foods, an indicator of diet quality, approached significance ( p  = 0.056) as an inverse predictor of urinary AFM1 detection. The findings augur the need for interventions that will improve food safety in Haiti and limit exposure to AFs, particularly among rural communities.